Implementation of Continuity of Care Through Family Emotional Support for Ischemic Stroke Patients - Rini Usman; Budhi Mulyadi; Mahathir Mahathir (Jurnal Ilmu Keperawatan Jiwa, 2020)
Stroke is a cerebrovascular disease. Ischemic stroke occurs when a blood vessel that supplies blood to the brain is blocked by a blood clot. The purpose of this study was to determine the relationship between family emotional support and the implementation of Continuity of Care for ischemic stroke patients in RSUP. DR. M. Djamil Padang. This research is a descriptive analytic cross sectional approach, sampling using a non-probability method with consecutive sampling technique, the sample is 123 according to the inclusion and exclusion criteria. Data collection using a questionnaire with Cronbach's alpha is 0.8> 0.01. Data analysis using chi square test. The test results showed that most of them provided good family emotional support. The results of the analysis showed that there was a significant relationship with p <0.05 between family support for the implementation of Continuity of Care. Based on the research, it can be concluded that optimal family emotional support increases the implementation of Continuity of Care and has an impact on improving the quality of life of stroke patients.